Intra‐African movements of the African cuckoo Cuculus gularis as revealed by satellite telemetry. (5th February 2018) - Iwajomo, Soladoye B.; Willemoes, Mikkel; Ottosson, Ulf; Strandberg, Roine; Thorup, Kasper
Abstract : Despite many bird species migrating regularly within the African continent, in response to rainfall and breeding opportunities, documented evidence of the spatiotemporal patterns of such movements is scarce. We use satellite telemetry to document the year round movement of an intra‐African migrant breeding in the savannah zone of sub‐Saharan Africa, the African cuckoo. After breeding in central Nigeria, the birds migrated to more forested sites in the Adamawa region of Cameroon (n = 2) and western Central African Republic (n = 1). Departure from the breeding ground coincided with deteriorating environmental conditions whereas arrival at the non‐breeding sites matched period of increasing vegetation greenness. Migratory movements generally occurred during dark hours. In total, an average distance of 748 km in 66 d was covered during the post‐breeding migration and 744 km in 27 d during return journey with considerable individual variation and with more stopover sites used during post‐breeding migration. The diversity of migration routes followed suggests a relatively variable or flexible initial migration strategy, high individual route consistency as well as high fidelity for non‐breeding grounds.